Differing Worldviews in Higher Education Two Scholars Argue Cooperatively About Justice Education - Arrows, Four.; Block, Walter; SpringerLink (Online service) (Rotterdam : SensePublishers, 2011)
Two noted professors on opposite sides of the cultural wars come together and engage in "cooperative argumentation." One, a "Jewish, atheist libertarian" and the other a "mixed blood American Indian" bring to the table two radically different worldviews to bear on the role of colleges and universities in studying social and ecological justice. The result is an entertaining and enlightening journey that reveals surprising connections and previously misunderstood rationales that may be at the root of a world too polarized to function sanely.
Keywords: Education; Education, Higher; Education; Higher Education